END-USER SOFTWARE ENGINEERING. - Burnett, Margaret; Cook, Curtis; Rothermel, Gregg (Communications of the ACM, 2004)
End-user programming has become the most common form of programming in use today [2], but there has been little investigation into the dependability of the programs end users create. This is problematic because the dependability of these programs can be very important; in some cases, errors in end-user programs, such as formula errors in spreadsheets, have cost millions of dollars. (For example, see www.theregister.co.uk/content/67/31298.html or panko.cba.hawaii.edu/ssr/Mypapers/whatknow.htm.) We have been investigating ways to address this problem by developing a software engineering paradigm viable for end-user programming, an approach we call end-user software engineering.